2matrix: A utility for indel coding and phylogenetic matrix concatenation1. (7th January 2014) - Salinas, Nelson R.; Little, Damon P.
Abstract : Premise of the study: Phylogenetic analysis of DNA and amino acid sequences requires the creation of files formatted specifically for each analysis package. Programs currently available cannot simultaneously code inferred insertion/deletion (indel) events in sequence alignments and concatenate data sets. Methods and Results: A novel Perl script, 2matrix, was created to concatenate matrices of non‐molecular characters and/or aligned sequences and to code indels. 2matrix outputs a variety of formats compatible with popular phylogenetic programs. Conclusions: 2matrix efficiently codes indels and concatenates matrices of sequences and non‐molecular data. It is available for free download under a GPL (General Public License) open source license (https://github.com/nrsalinas/2matrix/archive/master.zip ).